EFEKTIVITAS PENGGUNAAN “BUKU SAKU CALON PENGANTIN SEHAT” DALAM PERSIAPAN PRAKONSEPI - Rezah Andriani; Ria Gustirini; Fadilah Zhafarina (LPPM Universitas Abdurrab, 2026)
Reproductive health issues in Indonesia still require special attention because they have not been fully addressed. This is evident in the high rate of early marriage. According to data from the Religious Courts Agency, there were 50,673 dispensations for early marriage in Indonesia in 2022, a 17.54% decrease from the 61,449 cases in 2021. The high incidence of teenage pregnancy (16.19%) and the low level of adolescent knowledge about reproductive health remain. Reproductive health education provided to prospective brides is an effort to fulfill reproductive rights for women. The purpose of this study was to determine the effectiveness of using the